Fistula Program Management using DHIS2: Experience of Fistula Care Plus Project in Bangladesh - Uddin, Masum Salah; Huda, Sk Nazmul (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To share the experience of using DHIS2 in managing the Fistula Care Plus Project in Bangladesh. Methods: Since the beginning of the Fistula Care Plus Project in Bangladesh, we used DHIS2 for capturing cluster data from organizational units. Program data was entered in a customized DHIS2 platform on a quarterly basis. Program data was analyzed and shared with / disseminated to project partners and stakeholders on a regular basis. Directorate General of Health Services (DGHS) also included seven fistula related indicators for collecting fistula data from all the facilities across the country. Results: We were able to capture and manage 100% of project data using DHIS2 throughout the project period. Fistula data reported at governmental platforms was negligible. Through a structured process called “clinical data for decision making (CDDM)”, project partners were given critical insights for quality monitoring and upholding performance. DHIS2 based performance analysis was also found very helpful for project monitoring. Conclusion: DHIS2 was found to be very effective for fistula program management. Effective use of DHIS2 for fistula data management by the facilities throughout the country under the DGHS would require training and capacity building inputs.